The quiet eye supports error recovery in golf putting. (July 2017) - Walters-Symons, R.M.; Wilson, M.R.; Vine, S.J.
Abstract: Objectives: The aim of this study was to further examine the relationship between the Quiet eye (QE, Vickers, 1996) and performance. We aimed to scrutinise the relationship between QE and shot outcome and replicate the robust relationship between QE and expertise. Based on recent findings (Cooke et al., 2015) showing that motor planning is dependent upon the outcome of a previous attempt, we wanted to examine the influence of prior performance on the functionality of the QE. Design: We performed a 2 (expertise) x 2 (outcome) mixed design study. Participants performed golf putts until they had achieved 5 successful (hits) and 5 unsuccessful (misses) attempts. Methods: 18 experienced and 21 novice golfers participated in the study. Putts were taken from ten feet while wearing a mobile eye tracker. Results: Experienced golfers had consistently longer QE durations than novices but there was no difference in QE between randomly chosen hits and misses. However, QE durations were significantly longer on hits directly following a miss, but significantly shorter on misses following a miss. Conclusions: This is the first study to have examined QE duration as a consequence of prior performance. Our findings highlight the important role of QE in recovering from an error and improving performance. The findings add further support for the response programming function of the QE, as additional 'programming' was needed to recover from an error. Findings also highlight the potential for a link between QE and the allocation of attentional resources to the task (effort). Highlights: Experienced golfers had longer Quiet Eye (QE) durations than novice golfers. QE did not predict outcome when hit and missed shots were randomly selected. QE was longer for successful shots that followed a missed shot. QE was shorter for missed shots that followed a missed shot. This is the first study to have examined QE duration as a consequence of prior performance.